2013
DOI: 10.1167/13.13.26
|View full text |Cite
|
Sign up to set email alerts
|

Temporal channels and disparity representations in stereoscopic depth perception

Abstract: Stereoscopic depth perception is supported by a combination of correlation-based and match-based representations of binocular disparity. It also relies on both transient and sustained temporal channels of the visual system. Previous studies suggest that the relative contribution of the correlation-based representation (over the match-based representation) and the transient channel (over the sustained channel) to depth perception increases with the disparity magnitude. The mechanisms of the correlation-based an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(89 citation statements)
references
References 68 publications
7
82
0
Order By: Relevance
“…Nonetheless, since the model prediction was made without any parameter fitting, this success provides strong evidence that V1 cells signal disparity in these stimuli by exploiting fluctuations in local correlation within the RF. Note that if responses to halfmatched stimuli represented a contribution from a pure "matching computation" (Doi et al, 2011(Doi et al, , 2013Abdolrahmani et al, 2016;Henriksen et al, 2016a), the data in Figure 5 should lie on the identity line, which they do not.…”
Section: ϫ12mentioning
confidence: 94%
See 3 more Smart Citations
“…Nonetheless, since the model prediction was made without any parameter fitting, this success provides strong evidence that V1 cells signal disparity in these stimuli by exploiting fluctuations in local correlation within the RF. Note that if responses to halfmatched stimuli represented a contribution from a pure "matching computation" (Doi et al, 2011(Doi et al, , 2013Abdolrahmani et al, 2016;Henriksen et al, 2016a), the data in Figure 5 should lie on the identity line, which they do not.…”
Section: ϫ12mentioning
confidence: 94%
“…The original binocular energy model does not signal depth in half-matched stereograms because its response varies linearly as a function of binocular correlation. Thus, when the mean binocular correlation is zero, the mean response of the model is equal to its uncorrelated response (although the variability of the response is greater in the halfmatched case; Doi et al, 2013;Doi and Fujita, 2014;Henriksen et al, 2016a). The extent of this variation in binocular correlation will depend on the number of dots contained within the receptive field.…”
Section: Model Disparity-tuning Curvesmentioning
confidence: 99%
See 2 more Smart Citations
“…V1 neurons approximately implement a 'correlationbased' computation, but the results with anticorrelated dots indicate that their response is not a linear function of binocular correlation-it is not a 'pure correlation' computation. Recently, an ingenious series of psychophysical experiments by Doi et al [47,48] have demonstrated that human stereo matching in some stimuli cannot be explained by a matching scheme based on pure correlation. They have suggested that this requires two separate matching mechanisms, and show that a model with two mechanisms neatly describes the data [49].…”
Section: Summary and Implicationsmentioning
confidence: 99%